Intravascular lymphoma forming massive aortic tumors complicated with sarcoidosis and focal segmental glomerulosclerosis: a case report and literature review - Oda, Yasuhiro (BMC Nephrol, 2018)
BACKGROUND: Intravascular large B-cell lymphoma (IVLBCL) is a rare subtype of extranodal diffuse large B-cell lymphoma characterized by proliferation of B cells within small vessels. Herein, we report a case of a 77-year-old man who presented with IVLBCL and massive tumor formation on the aortic wall who was previously diagnosed with sarcoidosis and focal segmental glomerulosclerosis (FSGS). To our knowledge, this is the first reported case of an IVLBCL with aortic tumor formation. CASE PRESENTATION: A 77-year-old ambulatory man with sarcoidosis and FSGS had neurological symptoms for nine months. The patient presented to the emergency department with sudden left leg pain, and was diagnosed with acute femoral artery occlusion. Emergency thrombectomy was performed subsequently. Pathological evaluation of the thrombi revealed that its surface was filled with large atypical B cells. Bone marrow biopsy showed infiltration of large atypical B cells within the small vessels. IVLBCL was suspected and further examination was planned, but the patient died due to sudden respiratory and cardiac arrest on hospital day twelve. Autopsy revealed intravascular tumors adherent to the aortic arch, left ventricle, and the abdominal aorta. All enlarged lymph nodes and the ventricular septum of the heart showed hyalinized lesions with granular formation consistent with sarcoidosis. The patient was diagnosed with IVLBCL with aortic tumor formation complicated with sarcoidosis and FSGS. CONCLUSIONS: IVLBCL may present with tumor formation on the aortic wall. Although the cause of its affinity to the aortic wall is yet unknown, autopsy findings imply that arteriosclerosis may have contributed to the tumor formation. The literature suggests that T-cell abnormalities could possibly be the common etiology of intravascular lymphoma, sarcoidosis, and FSGS.